Cobalt-catalyzed stereoselective iodosulfonylation and diiodination of alkynes via oxidation of potassium iodide in air. Issue 13 (29th March 2018) - Taniguchi, Nobukazu
Abstract: Cobalt-catalyzed iodosulfonylation of alkynes can be achieved using sodium sulfinates in the presence of KI. This procedure produces numerous stereoselective ( E )- β -iodoalkenyl sulfones with good yields and suppresses the formation of diiodoalkenes. Furthermore, when this reaction is performed in the absence of sodium sulfinates, the expected ( E )-diiodoalkenes are obtained. Graphical abstract: